Demographic, Epidemiologic and Clinical Analyses of Paediatric Patients Hospitalized with Henoch-Schonlein Purpura: A Retrospective Study - Şule Gökçe; Burçe Emine Dörtkardeşler; Aslı Aslan (Galenos Yayinevi, 2021)
Aim:Henoch-Schönlein purpura (HSP) is the most common systemic vasculitis in children. The purpose of this study was to assess the clinical, epidemiological, and laboratory features of 117 children diagnosed with HSP.Materials and Methods:This study was conducted to evaluate the data of 117 children with HSP, retrospectively. The presence of the cardinal clinical findings such as purpura, abdominal pain, and arthralgia; and the presence of increased erythrocyte sedimentation rate, decreased serum C3 levels, leukocytosis, blood in the stool, haematuria, and proteinuria were assessed in children with HSP.Results:Of the 117 patients enrolled in the study, 68 were males (58.1%) and 49 were females (41.9%). The median age was 85 (49) months. Purpuric skin lesions were detected in ninety-eight (97.9%) patients, arthritis/arthralgia in 71 (60.6%), gastrointestinal involvement in 52 (44.4%), and renal involvement in 27 (23%) patients. The median duration of hospitalization day was 6 (10) days. Non-palpable purpuric skin lesions mostly located on ankles were the most common involvement in the patients.Conclusion:Non-palpable purpuric skin lesions were the most common presentations followed by arthritis/arthralgia, and gastrointestinal involvement in our patients. Seasonal distributions, gender, and ages of the patients were concluded to be noncontradictory compared with the literature. Although variable clinical findings in the patients were found, the cardinal features of HSP were determined in almost all subjects in this study.